حوكمة المرفق العمومي كبديل أساسي لترقية الخدمة العمومية - حمايتي صباح (جامعة الوادي University of Eloued, 2024)
من خلال هذه الورقة البحثية تم تسليط الضوء على تكريس مفهوم الحوكمة الجيدة كأحد أهم المفاهيم الإدارية الحديثة كما أنها تعتبركألية لتحديث و ترقية الخدمة العمومية وخاصة أنها تكتسي أهمية كبرى في ظل التحولات و التطورات التي لحقت الدولة في ظل الأزمات التى يتخبط فيها المرفق العام، فحوكمة المرفق العام هو تكريس مبادئها ضمن أساليب التسيير قصد الرفع من مستوى أداء الخدمة العمومية ، كما أنها تعتمد على إشراك فواعل (الدولة ، المجتمع المدني ، القطاع الخاص ) إلى جانبها من أجل الوصول على خدمة عمومية ناجعة متجاوزة بذلك الصعوبات التى تواجهها هذه الأخيرة . This research paper aims to shed light on establishing the concept of good governance as one of the most important modern administrative concepts. It is also considered a mechanism for modernizing and upgrading the public service, especially since it is of great importance in light of the transformations and developments that have befallen the state in light of the crises in which the public facility is floundering. The governance of the public facility It is to enshrine its principles within management methods in order to raise the level of public service performance. It also depends on the involvement of actors (the state, civil society, the private sector) alongside it in order to achieve an effective public service, thus overcoming the difficulties faced by the latter.
Governance of the public utility as a basic alternative to promoting public service
Keywords: الخدمة العمومية; الحوكمة; الدولة; القطاع الخاص; المجتمع المدني; Public service; governance; private sector; civil society